EFFECT OF CUSTOMER SERVICE, PRICE AND PRODUCT COMPLETENESS TO CUSTOMER LOYALTY COSMETICS AT KITA COSMETICS STORE PONTIANAK - Jihan Safhiran (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2022)
Abstract: Local and foreign cosmetic companies are currently targeting Indonesia as their market share. For women today, cosmetics are a vital and main part of their daily lives, in order to obtain and maintain their beauty from time to time. Every cosmetic created and manufactured certainly has its own distinct advantages to be able to fulfill the desires and needs of its consumers. In Indonesia, various brands are now available from foreign and local cosmetic manufacturers. The purpose of this study is to determine the effect of customer service on the loyalty of cosmetic customers at the Kita Pontianak Store, to determine the effect of price on the loyalty of cosmetic customers at the Kita Pontianak Store and to determine the effect of product completeness on the loyalty of cosmetic customers at the shop Kita Pontianak. This research method is associative. Data collection techniques: questionnaires and documentary studies. The sample taken was based on the research criteria, namely the respondent had at least 2 purchases of cosmetics at the Kita Store Pontianak on Jalan Jenderal Sudirman with purposive sampling. The results showed from the data analysis carried out with multiple regression that there was an effect of customer service, price and product completeness partially on cosmetic customer loyalty at Toko Kita Pontianak.